2005
DOI: 10.1063/1.1872209
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic properties of three-dimensional ZnO hybrid structure

Abstract: Three-dimensional (3D) ZnO hybrid structure was fabricated by growing a ZnO buffer layer, a ZnO nanowire array, and a ZnO film continuously through the control of supersaturation conditions. Lower and upper ends of vertically aligned nanowires in this hybrid structure formed seamless interfacial contacts with the buffer layer and the film for current conduction. Photocurrent was generated only when the ultraviolet (UV) light (λ=350nm) was irradiated. This structure also exhibited different atmosphere-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 11 publications
2
37
1
Order By: Relevance
“…It is natural to imagine that this oxidation process reduced the Zn vapor concentration in the growth chamber. In fact, some authors [24,25] have reported the transition from film growth to nanowire growth by altering the Zn vapor supersaturation level. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is natural to imagine that this oxidation process reduced the Zn vapor concentration in the growth chamber. In fact, some authors [24,25] have reported the transition from film growth to nanowire growth by altering the Zn vapor supersaturation level. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High supersaturation level usually results in a lateral growth mode [24][25][26], and hence the formation of a thick ZnO film was favored at this stage. The pre-coated template layer provides nucleation sites and guides the growth directions of the crystallites.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Single ZnO nanowires have been widely investigated for their potential applications to atomic force microscopy (AFM) cantilevers [15], gas sensors [16,17], nanotransistors [18], and logic gate devices [19]. The heterostructures of n-ZnO nanorods on p-GaN for LED applications [20][21][22][23][24] and high power operating nanodevices [25] have also been studied. However, for industrial applications of nanostructures, several tens-thousands of the nanostructures should be used for a single device because practical devices require reproducibility, stability and durability.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide nanomaterials have attracted a considerable attention in the past few decades due to their potential applications in optics [15], optoelectronics [16], photoelectric devices [17], solar cells [18], catalysis [19] and sensors [20]. ZnO is a well-known semiconductor material with a wide band gap of 3.37 eV [21] and large excitonic binding energy of 60 meV [22].…”
mentioning
confidence: 99%